Analisis Budaya Pelaporan Insiden Keselamatan Pasien Pada Perawat di Rumah Sakit Umum Daerah (RSUD) Sawerigading Palopo - Patmawati, Try Ayu; R Djano, Nur Asphina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to analyze the culture of incident reporting of patient safety to nurses at the Sawerigading Palopo Hospital.Methods: This article used descriptive analytic with a cross sectional design. The population in this study were nurses at Sawerigading Palopo Hospital with a sample of this study as many as 63 nurses, sampling using purposive sampling technique. The instrument used was the IRCQ (Incident Reporting Culture Questionnaire).Results: This study was found that from 63 respondents there were 38 respondents (60.3%) who showed a negative response to incident reporting culture and positive response about 25 people (39.7%). Based on the subscale, the factor that received the greatest negative response was the factor